2020
DOI: 10.5614/jpwk.2020.31.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Live-Work Housing Concept for Rusunawa in Indonesia: Is it Possible?

Abstract: Living and working in the same unit is part of the everyday life of low-income people who live in slum areas to overcome their economic situation. However, when they are evicted from slums and relocated to Rusunawa (vertical public rental housing), their live-work life is no longer possible. Empirically, living in Rusunawa puts many residents in financial difficulties. This article is aimed to investigate the feasibility of a live-work housing concept for Rusunawa.Based on observations at Rusunawa Pesakih in W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…Many researchers have engaged in academic research on mixed-use villages, and their research directions can be summarized as follows: (1) Regional growth perspective-Kong et al proposed the concept of "working and living integration" as a driving force behind regional growth, providing empirical evidence through using productive rural settlements in the Yangtze River Delta region as examples [19]. (2) Economic development perspective-Triyuliana et al analyzed the feedback effect of private individual's operational methods [20], such as family workshops, on rural economy and human settlement development in industrial villages. (3) Urban-Rural construction perspective-Chen et al elucidated the current situation of mixed functions in villages [21], highlighting the synergistic effect of rural industrial development and urban-rural construction.…”
Section: Mixed-use Villagesmentioning
confidence: 99%
“…Many researchers have engaged in academic research on mixed-use villages, and their research directions can be summarized as follows: (1) Regional growth perspective-Kong et al proposed the concept of "working and living integration" as a driving force behind regional growth, providing empirical evidence through using productive rural settlements in the Yangtze River Delta region as examples [19]. (2) Economic development perspective-Triyuliana et al analyzed the feedback effect of private individual's operational methods [20], such as family workshops, on rural economy and human settlement development in industrial villages. (3) Urban-Rural construction perspective-Chen et al elucidated the current situation of mixed functions in villages [21], highlighting the synergistic effect of rural industrial development and urban-rural construction.…”
Section: Mixed-use Villagesmentioning
confidence: 99%
“…Rusunawa)) is one of strategies to reduce backlogs in metropolitan areas (Kushendar et al, 2021;Sari, 2016). It is also viewed to be the right solution to the high demand for proper housing for mid-low-class families (Akinwande & Hui, 2022;Triyuliana & Prakoso, 2020).Rusunawa Dabag is one of the Housing simple rented flats in Yograkarta. Figure 1 showed the overview of Rusunawa Dabag and its location Map.…”
Section: Introductionmentioning
confidence: 99%
“…Kushendar (et al, 2021) also suggested the need management policy adaptation for Rusunawa to the social and economic conditions of the community, the demand for commitment and assistance from stakeholders to maintain financial and human resources, the requirement for website optimization as a media for information and communication, and the requirement to modify Rusunawa's organizational structure. Therefore, both the government, as the policy maker, and the residents of Rusunawa, as the policy's intended target, should take part in achieving the managed housing (Triyuliana & Prakoso, 2020).…”
Section: Introductionmentioning
confidence: 99%